Redesign of The Wireless Local Area Network (WLAN) at the Provincial Library Office of South Sumatra - Ifan (Penerbit Jurnal Indonesia, 2025)
The design of the Wireless Local Area Network (WLAN) at the South Sumatra Provincial Library Service (DISPUSTAKA) aims to evaluate the current internet connectivity performance. Currently, DISPUSTAKA provides Wi-Fi internet services for office use and within the provincial library facilities. Network connectivity testing is conducted using the Quality of Service (QoS) method with the help of applications such as Axence NetTools. The connectivity test aims to determine the actual speed and performance level of the Wi-Fi service provided by DISPUSTAKA. The collected QoS data are analyzed using the Action Research method. The design process begins with a needs analysis, including identifying the number of users, types of devices used, and the coverage area. A site survey is then carried out to understand the building layout and identify potential physical barriers that may affect Wi-Fi signal propagation from the Access Point devices. Based on these findings, the researcher proceeds to redesign the existing WLAN to provide more reliable and stable connectivity services, thereby improving internet performance to support the operations of the South Sumatra Provincial Government.